2022
DOI: 10.1007/s00167-022-07023-1
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan based scaffold applied in patellar cartilage lesions showed positive clinical and MRI results at minimum 2 years of follow up

Abstract: Purpose New scafold-based cartilage regeneration techniques have been developed to improve the results of microfractures also in complex locations like the patello-femoral joint. The aim of this study was to analyse the results obtained in patellar lesions treated with a bioscafold, a mixture composed by a chitosan solution, a bufer, and the patient's whole blood which forms a stable clot into the lesion. Methods Fifteen patients with ICRS grade 3-4 cartilage lesions of the patellar surface were treated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 27 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…Similarly, MR also showed positive results in terms of tissue repair evaluated through the MOCART 2.0 score. This is an important finding that testifies the persistence of the repair tissue quality at mid‐term follow‐up, which was also compared to values previously documented in the short‐term [ 38 ]. Still, previous studies showed a poor correlation between this score and the patient's symptoms [ 13 , 27 ].…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Similarly, MR also showed positive results in terms of tissue repair evaluated through the MOCART 2.0 score. This is an important finding that testifies the persistence of the repair tissue quality at mid‐term follow‐up, which was also compared to values previously documented in the short‐term [ 38 ]. Still, previous studies showed a poor correlation between this score and the patient's symptoms [ 13 , 27 ].…”
Section: Discussionsupporting
confidence: 53%
“…Scaffolds can be based on different types of matrices, such as collagen [ 3 ], hyaluronic acid [ 50 ] or chitosan, as the scaffold evaluated in the current study [ 38 ]. This chitosan‐based scaffold already showed to provide promising clinical results and improved cartilage repair compared to microfractures for the treatment of condylar cartilage lesions [ 41 , 43 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations